2015
DOI: 10.1177/0269216315578990
|View full text |Cite
|
Sign up to set email alerts
|

Patient and carer experiences of clinical uncertainty and deterioration, in the face of limited reversibility: A comparative observational study of the AMBER care bundle

Abstract: Background:Clinical uncertainty is emotionally challenging for patients and carers and creates additional pressures for those clinicians in acute hospitals. The AMBER care bundle was designed to improve care for patients identified as clinically unstable, deteriorating, with limited reversibility and at risk of dying in the next 1–2 months.Aim:To examine the experience of care supported by the AMBER care bundle compared to standard care in the context of clinical uncertainty, deterioration and limited reversib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
61
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(62 citation statements)
references
References 32 publications
(35 reference statements)
0
61
0
1
Order By: Relevance
“…We conducted the first comparative observational mixed-methods study of the AMBER care bundle and identified a mixed picture. 48 First, the AMBER care bundle was associated with increased frequency of discussions about prognosis between clinicians and patients, and higher awareness of their prognosis by patients. Second, we observed that those patients who died in locations other than hospitals had shorter lengths of stay than those who received usual care.…”
Section: The Management Of Clinical Uncertainty In Hospital Settingsmentioning
confidence: 99%
“…We conducted the first comparative observational mixed-methods study of the AMBER care bundle and identified a mixed picture. 48 First, the AMBER care bundle was associated with increased frequency of discussions about prognosis between clinicians and patients, and higher awareness of their prognosis by patients. Second, we observed that those patients who died in locations other than hospitals had shorter lengths of stay than those who received usual care.…”
Section: The Management Of Clinical Uncertainty In Hospital Settingsmentioning
confidence: 99%
“…The care bundle, which includes roles for the entire medical team emphasises clear communication and planning. This approach is promising and recent research suggests that there may be some benefits; awareness of prognosis appeared to be higher among patients supported by the AMBER care bundle 35. However, a full evaluation of the efficacy of this approach is needed.…”
Section: Addressing Uncertainty: Current Strategiesmentioning
confidence: 99%
“…Critical illness, related or unrelated to underlying disease pathology, creates further uncertainty for clinicians because there are unknown elements in disease processes and prognostication (Bristowe et al., ; Pattison et al., ). Previous ethnographic work in the critical care unit suggests that there are debilitating emotional consequences for those involved in decisions (Seymour, ), especially where conflict arises (Higginson et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…This is evidenced by a large review of 1.2 million admissions where the mean number of admissions in the last 12 months of life averaged 2.28, leading to 30.05 bed days occupied (Bardsley, Georghiou, Spence, & Billings, 2016). Critical illness, related or unrelated to underlying disease pathology, creates further uncertainty for clinicians because there are unknown elements in disease processes and prognostication (Bristowe et al, 2015;Pattison et al, 2015). Previous ethnographic work in the critical care unit suggests that there are debilitating emotional consequences for those involved in decisions (Seymour, 1999), especially where conflict arises (Higginson et al, 2016).…”
mentioning
confidence: 99%